OPTIMIZING HEAVY EQUIPMENT PRODUCTIVITY BASED ON CYCLE TIME ON THE XYZ ROAD PROJECT (Science and Technology (SciTech), 2023)
The XYZ road project is an important and busy road project in the Jawa region. During the slope stabilization work in the project, there was a problem with inefficient use of heavy equipment in the field. This resulted in some heavy equipment not working optimally in the field. This problem can affect the project's time and cost. Ideally, the amount of heavy equipment used should be in accordance with the volume of work. Based on the analysis results, the productivity of heavy equipment for embankment work in slope stabilization is: Excavator = 73.87 m3/hour = 517.10 m3/day, Dump Truck = 10.87 m3/hour = 76.09 m3/day, Bulldozer = 96.74 m3/hour = 677.2 m3/day, Vibrator Roller = 132.59 m3/hour = 928.148 m3/day. The appropriate and optimal heavy equipment composition to use is 1 unit of excavator, 7 units of dump truck, 1 unit of bulldozer, 1 unit of vibrator roller. The time required to complete the embankment work in slope stabilization is by using the second alternative, which is 14 working days faster than the planned time and completed within 28 days